2020
DOI: 10.3171/2019.7.peds19305
|View full text |Cite
|
Sign up to set email alerts
|

Management of sterile abdominal pseudocysts related to ventriculoperitoneal shunts

Abstract: OBJECTIVEThere are many known complications associated with CSF shunts. One of the more rare ones is a sterile abdominal pseudocyst due to decreased peritoneal absorption. This study was undertaken to detail the presentation, evaluation, and management of this unusual shunt-related event.METHODSPatients presenting with ventriculoperitoneal shunt (VPS)–related sterile abdominal pseudocysts treated at two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As opposed to shunt removal and external ventricular drain (EVD) insertion, however, shunt externalization avoids the need to access or remove the proximal catheter or valve. This procedure has become a core component in the management of shunt infections, 3 abdominal pseudocysts, 4 and other abdominal complications.…”
mentioning
confidence: 99%
“…As opposed to shunt removal and external ventricular drain (EVD) insertion, however, shunt externalization avoids the need to access or remove the proximal catheter or valve. This procedure has become a core component in the management of shunt infections, 3 abdominal pseudocysts, 4 and other abdominal complications.…”
mentioning
confidence: 99%
“…2 Some treatment algorithms have been described for the management of abdominal pseudocysts. 21,22 The shunt tap is the most vital step in the confirmation of further treatment requirements. If infection is initially eliminated, distal catheter repositioning is the only suitable method for the treatment of patients with sterile abdominal pseudocysts.…”
mentioning
confidence: 99%
“…If the CSF is sterile, the peritoneal cavity, pleural space, atrium, or gallbladder can be used to reposition the distal catheter for patients who remain shunt-dependent. 22 Reaccumulation of pseudocysts remains a challenge for pediatric patients with abdominal pseudocysts who have undergone fluid drainage followed by the externalization or revision of shunts. 1 In a literature review of adult cases with hepatic pseudocysts, Dabdoub et al observed no recurrences after the revision of the shunt, even in cases of infection.…”
mentioning
confidence: 99%